PEMAHAMAN KESETARAAN GENDER - Indar Wahyuni; Riyanto Riyanto (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2019)
The increasing number of divorce cases from year to year at Pati Religious Court indicates an increase in the quantity and quality of wife's dissatisfaction with their marriages, especially their husbands, who do not associate them well, do not carry out their duties and obligations properly, and husbands who act harshly towards his wife, so that there were cases of domestic violence. The courage of the wife to file a divorce which is the focus of this research is to be further investigated whether there is an understanding of gender equality that influences his decision. This research is a field research (field research), this research is descriptive analytic, namely an investigation that tells, analyzes and classifies data qualitatively. The source of primary data is data obtained from interviews with judges who decided on divorce cases in PA Kab Pati, and women who divorced. Data collection uses the method of documentation and interviews. In the interview, a sampling method is used, namely a purposive sampling system. Here, the author does not interview all existing judges and informants (divorce actors), but rather chooses judges and divorced informants who can represent several categories according to the research design and are representative to be used as data sources. In the process of finding data to maintain its validity, triangulation is carried out, namely checking the degree of trust in information both in terms of technique, source and time. Data are analyzed qualitatively using inductive and interpretative analysis instruments. This inductive and interpretative way of thinking is used in order to build a conception of interpretation regarding the high divorce proposed by women in PA Pati and its causal factors. The results of this study that gender understanding for informants who filed for divorce in Pati Regency PA was shown from their awareness of their rights in marriage. This can be seen from their responses to understand the concept of marriage, gender roles in the family and domestic violence. So that their rights must be fought because they do not want to dissolve in painful household shackles. Thus the understanding of gender influences the high divorce in Pati Regency. The factors causing divorce in the District of Religion Religious Court in 2015, 2016, 2017 and 2018 in August were due to one leaving the party and no responsibility at the same time being the highest cause. The cause of the moral crisis was ranked second, then economic factors, jealousy, constant quarrels and disputes, domestic violence, and the presence of parents who forced their children to marry. This is in line with the factors that caused informants to file for divorce.